Robust voltage regulation control of a small-scale microgrid testbed - Low, Chang Hong (2017)
Microgrids are increasingly deployed around the world to serve the needs of small rural communities as a low cost electrification solution that reduces the need for transmission and distribution infrastructure. However, voltage control of Microgrids can be a tricky issue due to intermittence of power supply, which generally rely heavily on renewable energy sources. Therefore, this project aims to develop a robust voltage control solution by exploring 2 control schemes on a small-scale AC microgrid testbed. The first scheme applies Park's transformation to convert the three phase AC waveform to DC quantities before application of PID control. The second method involves state space representation of the system and applying an appropriate dynamic state feedback to steer the output to a desired state. The report will first address development of the microgrid testbed and the computer interface implementing the control algorithm. It is followed up by the implementation of the control scheme and subsequent analysis of the experimental results.